1985
DOI: 10.1177/002205748516700301
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological Development and the Politics of Talk in Family Life

Abstract: One hundred and thirty-five women from all walks of life—some enrolled in colleges, others in programs to enhance parenting skills—were interviewed to trace women's natural epistemologies or their ways of thinking about thinking and about themselves as knowers. We describe five different ways of knowing that women use to make sense out of their experience in the world. We also examine the descriptions that the women gave of the patterns of communication in their families. The politics of talk in family life pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The authors, recognizing that males are often rhetorically dominant in face-to-face classes, wonder if females' preference for on-line learning might relate to their ability to be heard. Much literature has pointed out the value, to women, of claiming their voices (Gilligan, 1982;Belenkey, 1997). On-line learning gives each person an equal chance to contribute to discussion, without being interrupted or out-shouted.…”
Section: Gendermentioning
confidence: 99%
“…The authors, recognizing that males are often rhetorically dominant in face-to-face classes, wonder if females' preference for on-line learning might relate to their ability to be heard. Much literature has pointed out the value, to women, of claiming their voices (Gilligan, 1982;Belenkey, 1997). On-line learning gives each person an equal chance to contribute to discussion, without being interrupted or out-shouted.…”
Section: Gendermentioning
confidence: 99%
“…For example, in the United States, the number of women enrolled in college increased from approximately 3 million in 1970 to 8.6 million in 1998 (U.S. Department of the Census, 2002 Educational research and practice has, similarly, been evolving. Although subsequent research found that both men and women reasoned from an ethic of care as well as justice, Gilligan's work was a turning point in research that sought to better understand women's and girls' development and "ways of knowing" (Belenky et al, 1985) as distinct from the ways in which men and boys developed and thought about the world. This oversight stimulated research that focused on women and girls and how their experiences and development differed from that of men and boys (Belenky, Clinchy, Goldberger, & Tarule, 1985).…”
Section: -2mentioning
confidence: 99%
“…In her text The Psychological Development of Girls and Women: Rethinking Change in Time, Sheila Greene argues for the adop-behaviors and thoughts of men and boys to women and girls. This oversight stimulated research that focused on women and girls and how their experiences and development differed from that of men and boys (Belenky, Clinchy, Goldberger, & Tarule, 1985). One piece of seminal work was that done by Carol Gilligan, who in 1982 argued that women reasoned in "a different voice" than men, relying on an "ethic of care" and concern with relationships rather than an "ethic of justice" and logic when making moral decisions.…”
Section: Time After Timementioning
confidence: 99%
See 1 more Smart Citation
“…By the way, Belenky et al claim that they studied only women because William Perry had already studied men. 27 This reason is inadequate; for one thing, comparing women and men requires that both be interviewed by the same researchers who use the same techniques under the same conditions. The four researchers carrying out the Women's Ways project seem to have had enough woman power to interview some men.…”
Section: Women's Ways Of Fudgingmentioning
confidence: 99%